2015
DOI: 10.1021/acs.chemrestox.5b00405
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cytochrome P450 Reductase Deficiency on 2-Amino-9H-pyrido[2,3-b]indole Metabolism and DNA Adduct Formation in Liver and Extrahepatic Tissues of Mice

Abstract: 2-Amino-9H-pyrido[2,3-b]indole (AαC), a carcinogen formed during the combustion of tobacco and cooking of meat, undergoes cytochrome P450 (P450) metabolism to form the DNA adduct N-(deoxyguanosin-8-yl)-2-amino-9H-pyrido[2,3-b]indole (dG-C8-AαC). We evaluated the roles of P450 expressed in the liver and intestine to bioactivate AαC by employing male B6 wild-type (WT) mice, liver-specific P450 reductase (Cpr)-null (LCN) mice, and intestinal epithelium-specific Cpr-null (IECN) mice. Pharmacokinetic parameters wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 63 publications
0
32
0
Order By: Relevance
“…41 The level of DNA adduct formation of AαC in liver was also unaffected in the liver specific P-450 reductase null mice treated with high doses of AαC. 43 Our data show that the contribution of non-P450 oxidases to the metabolism of AαC and bioactivation in human hepatocytes is minor.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…41 The level of DNA adduct formation of AαC in liver was also unaffected in the liver specific P-450 reductase null mice treated with high doses of AαC. 43 Our data show that the contribution of non-P450 oxidases to the metabolism of AαC and bioactivation in human hepatocytes is minor.…”
Section: Discussionmentioning
confidence: 72%
“…The UV spectra of each hydrolysis products was compared to those spectra of AαC-6-OH and AαC-3-OH, which were produced using human liver microsome as previously reported. 34,41 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Urinary concentrations of PhIP and the two beta-carboline HCAAs evaluated, harman and norharman, were similar in smokers and non-smokers. As there are reports that the half-lives of HCAA are relatively short (< 24 hours), the urinary HCAA levels probably reflect the short-term exposure to HCAA [27, 28]. Measurement of HCAA in hair could be an alternative analysis to determine the long-term exposure to HCAA.…”
Section: Resultsmentioning
confidence: 99%
“…1114 Moreover, high levels of DNA adducts are detected in the liver, colon and other extrahepatic tissues of mice upon AαC treatment. 13,15,16 The carcinogenic potential of AαC in humans is unknown, however, AαC is genotoxic to human lymphoblastoid cells (MLC-5) and peripheral blood lymphocytes cells. 17,18 We previously reported that primary human hepatocytes also efficiently bioactivate AαC to its N -hydroxylated metabolite, 2-hydroxamino-9 H -pyrido[2,3-b]indole (HONH-AαC), 19,20 which binds to DNA and can lead to mutations.…”
Section: Introductionmentioning
confidence: 99%